2009
DOI: 10.1038/tpj.2009.68
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenases-1 and -2 differentially modulate leukocyte recruitment into the inflamed brain

Abstract: Peripheral leukocyte recruitment in neuroinflammatory conditions can exacerbate brain tissue damage by releasing cytotoxic mediators and by increasing vascular permeability. Cyclooxygenase (COX)-derived prostaglan-dins promote the migration of several immune cells in vitro, however, the specific roles of COX-1 and -2 on leukocyte recruitment in vivo have not been investigated. To examine the specific effects of COX-1 or COX-2 deficiency on neuroinflammation-induced leukocyte infiltration, we used a model of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 70 publications
3
46
0
1
Order By: Relevance
“…Additionally, the development of selective COX-2 inhibitors further suggests an important role for this cyclooxygenase in the BBB in response to acute inflammation; specifically, its inhibition lead to a decrease in the expression of tight junctions proteins in the endothelial cells of the barrier (Germann et al, 2008). In accordance, it has also been shown that COX-2 null-mice exhibit an increase in LPS-induced BBB disruption, mediated by an increase in matrix metalloproteinases 9 and 3 activities (Choi et al, 2010). These results further support the hypothesis that COX-2 may mediate the neuroinflammatory response, especially in maintaining the integrity of the neurovascular unit (Choi et al, 2010).…”
Section: The Choroid Plexus Response To Acute Peripheral Inflammationsupporting
confidence: 72%
See 1 more Smart Citation
“…Additionally, the development of selective COX-2 inhibitors further suggests an important role for this cyclooxygenase in the BBB in response to acute inflammation; specifically, its inhibition lead to a decrease in the expression of tight junctions proteins in the endothelial cells of the barrier (Germann et al, 2008). In accordance, it has also been shown that COX-2 null-mice exhibit an increase in LPS-induced BBB disruption, mediated by an increase in matrix metalloproteinases 9 and 3 activities (Choi et al, 2010). These results further support the hypothesis that COX-2 may mediate the neuroinflammatory response, especially in maintaining the integrity of the neurovascular unit (Choi et al, 2010).…”
Section: The Choroid Plexus Response To Acute Peripheral Inflammationsupporting
confidence: 72%
“…In accordance, it has also been shown that COX-2 null-mice exhibit an increase in LPS-induced BBB disruption, mediated by an increase in matrix metalloproteinases 9 and 3 activities (Choi et al, 2010). These results further support the hypothesis that COX-2 may mediate the neuroinflammatory response, especially in maintaining the integrity of the neurovascular unit (Choi et al, 2010). Finally, cyclooxygenases can differentially modulate leukocyte recruitment into the inflamed brain (Choi et al, 2010).…”
Section: The Choroid Plexus Response To Acute Peripheral Inflammationsupporting
confidence: 63%
“…Previous studies reported that Cox-derived PGs can modulate leukocyte migration to the inflamed tissue (52). Mice deficient in Cox-2 or mPGES-1, a downstream PG synthase, have a reduced recruitment of leukocytes to the inflammatory foci, as shown in different mouse models, including thioglycolate- induced peritonitis (53,54).…”
Section: Discussionmentioning
confidence: 89%
“…In contrast, in neurodegenerative diseases, COX-2 inhibitors are not protective in mouse models of Alzheimer disease (7) and did not show benefits in clinical trials in Alzheimer disease patients (8) or in patients with mild cognitive impairment (9). Furthermore, COX-2 inhibitors increase the risk of cardiovascular and cerebrovascular pathology (10), and Cox-2-deficient mice show exacerbated brain inflammation, leukocyte infiltration, and blood-brain barrier damage after exposure to the bacterial lipopolysaccharide (LPS) (11)(12)(13)(14)(15), suggesting some beneficial action of COX-2 in inflammation. Furthermore, COX-2 might contribute to neurovascular coupling because COX-2 inhibitors abrogate the increases in cerebral blood flow (CBF) induced by neuronal activation in rats (16).…”
mentioning
confidence: 99%